Comparison of Hematologic and Biochemical Factors between Women with Gestational Diabetes and Healthy Pregnant Women - Alireza Ahmadi; Mahdi Ghasemian; Ali asghar Ayatollahi; Murtadha Al-Khabori; seyedeh somayeh hosseini alarzi; Mohammad taher Hojjati (Medical Laboratory Journal, 2021)
Background and objectives: Diagnosis glucose intolerance in pregnancy is very important in preventing maternal and fetal complications. In this study, we compared hematological and biochemical characteristics of healthy pregnant women and women with gestational diabetes mellitus (GDM) to find predisposing and prognostic variables of GDM. Methods: In this study, 80 pregnant women (at 24-28 weeks of pregnancy) were divided into a GDM group and non-GDM group by performing oral glucose tolerance test using 75 g glucose according to the International Association of the Diabetes and Pregnancy Study Groups criteria. Results: The mean age of women with GDM was significantly higher than those without GDM (p=0.048). Other variables including body mass index, gestational age and daily sleep duration did not differ significantly between the two groups (P>0.05). There was a significant association between family history of diabetes and incidence of GDM (p=0.040). In addition, the C-peptide level was significantly higher in pregnant women with GDM (p=0.004). Conclusion: Considering the role of C-peptide in predicting metabolic syndrome, it is suggested to use this factor for identification of GDM patients.